CASE STUDY: THE STRENGTH AND WEAKNESS OF CORPORATE MERGERS AND ACQUISITIONS - Abel Zebada Hephzibah; Amelia Maximova Nababan; Nedichya Correia Belo (Problematika Hukum, 2024)
This study examines the impact of mergers and acquisitions (M&A) on company performance in emerging markets, using Indonesia as a case study. By analyzing data from the Business Competition Supervisory Commission (KPPU), it observes a significant rise in M&A activity during the pandemic. Unlike previous research, this study evaluates both short- and long-term effects on company performance, emphasizing the role of managerial ability (MA) in M&A success. While M&A offers benefits like diversification and access to new markets, it also poses risks such as unclear goals and cultural disparities. Successful M&A transactions can create value for shareholders, but careful planning, due diligence, and integration are essential for maximizing benefits and minimizing risksKeywords: Merger and acquisition, corporate, business competition, asset, financial transaction.